ChatGPT in The Lab: Analyzing the Potential Pros and Cons for Research Professionals - Boulaid, Fouad (Jurnal Arbitrer, 2023)
ChatGPT is a natural large language model developed by OpenAI, which generates human-like responses to a wide range of questions and prompts. For researchers, ChatGPT can provide quick and accurate answers to academic questions. The study delves into the nuanced landscape and scrutinizes the benefits and pitfalls associated with the usage of ChatGPT among higher education researchers. Based on a convenient sampling, the study involves a mixed-methods approach that includes both qualitative and quantitative data collection and analysis. One thousand ninety-nine researchers, who have used ChatGPT for various academic projects, are the subjects under study. The data was collected via online questionnaires and face-to-face interviews from four Moroccan universities and higher education institutions: Sultan Moulay Slimane University, Sidi Mohamed Ben Abdellah University, Moulay Ismail University, and Al Akhawayn University. The research data is processed and analyzed through the SPSS software and analyzed to discern patterns and trends in ChatGPT usage. The findings of the study underscore the multifaceted impact of ChatGPT in academic research. The outcomes show that the benefits of ChatGPT include its ability to provide quick and accurate responses to queries, facilitate learning and information-seeking, and enhance communication skills. In contrast, the pitfalls include its potential to lead to an overreliance on technology, reduced critical thinking skills, and the risk of plagiarism. Such a result has significant implications for the integration of ChatGPT into academic research practices. While acknowledging its advantages, researchers are urged to approach its use with caution, emphasizing the importance of maintaining a balance between technological assistance and the preservation of essential cognitive skills. The study provides insights into the ongoing discourse on the role of Chatbots in higher education and underscores the need for researchers to incorporate strategies that harness the benefits of ChatGPT while mitigating its potential drawbacks.